Introduction to the Application of Hand Crochet in Tweed Clothing—An Example of the Design of the 'White Velvet Shiyun Shang' - Ji, Enfeng (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
As more and more crochet designers around the world apply this traditional craft to a wider range of design fields, crochet has been transformed from a mere product of leisure activities to a commodity with fashion value. In this paper, we firstly analyse the design characteristics of handmade crochet in depth in order to interpret its technical connotation; Then, it explores the diversity of hand crochet stitches and their application in practice, and elaborates on the functionality of the technique; Subsequently, the paper analyses the expression of handmade crochet and its application in clothing design; Finally, taking the design of the 'White Velvet Shiyun Shang' series of tweed products as an example, the paper explains the design concept, design process, production process and display effect in detail, aiming to show the respect and inheritance of traditional Chinese culture. The paper is expected to inspire creators to use handmade crochet skills to outline and open up the infinite possibilities of life, and to arouse the public's deep affection and admiration for Chinese culture.